2017
DOI: 10.1193/051816eqs082m
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response Evaluation of Damped-Outrigger Systems with Various Heights

Abstract: Outriggers are a proven and effective system used to reduce the dynamic response of tall buildings. By inserting dampers into the outriggers, providing supplementary energy dissipation, further improvements in the dynamic response can be achieved. The aim of this study is to develop analytical methods for the dynamic response evaluation of a single-damped-outrigger system and determine the optimal outrigger locations and damper sizes to minimize response. Changes in the mode shape, damping, natural period and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 9 publications
4
31
0
Order By: Relevance
“…In addition, regardless the dampers size (damping coefficient), λ < 0.4 has less effect on improving the overall damping ratio of the building, if compared to values of λ > = 0.4. This observation is in agreement with the study of Huang and Takeuchi and suggests that an optimal location of the outrigger (λ OPT ) is somewhere between 0.4 and 0.9. It should be noticed, nevertheless, that the optimal damping varies with the mode, so no single outrigger location will lead to reduce the response of all the modes to its minimum .…”
Section: Parametric Study On the Factors Affecting The Performance Ofsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, regardless the dampers size (damping coefficient), λ < 0.4 has less effect on improving the overall damping ratio of the building, if compared to values of λ > = 0.4. This observation is in agreement with the study of Huang and Takeuchi and suggests that an optimal location of the outrigger (λ OPT ) is somewhere between 0.4 and 0.9. It should be noticed, nevertheless, that the optimal damping varies with the mode, so no single outrigger location will lead to reduce the response of all the modes to its minimum .…”
Section: Parametric Study On the Factors Affecting The Performance Ofsupporting
confidence: 93%
“…Although it has been suggested that damping ratio may exert a larger influence on the structural performance, peak responses may not be optimally reduced by assuming a λ OPT based on the increase of the damping ratio. If, for a given earthquake level, the peak inter‐story drift at each of the selected range of outrigger locations λ is plotted, then the inter‐story drift is reduced as λ increases (Figure a).…”
Section: Parametric Study On the Factors Affecting The Performance Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of a damped‐outrigger in reducing the seismic response was also verified experimentally . Huang and Takeuchi indicated that the optimal elevation of a damped‐outrigger incorporating viscous dampers ranges from 50% to 80% of the building height. In addition, the seismic performance of multioutrigger was also investigated .…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this experimental study, Zhou and Li performed further analyses to evaluate the dynamic response of two finite element (FE) models, representing the tested specimens, under various earthquake records. Huang and Takeuchi developed analytical methods to determine the optimal outrigger locations and damper sizes to minimize response and constructed a simplified single‐degree‐of‐freedom model. The experimental and analytical research on damped outriggers comprises not only the use of VDs as energy dissipation devices but also the use of buckling‐restrained braces (BRBs).…”
Section: Introductionmentioning
confidence: 99%